2016
DOI: 10.1097/aog.0000000000001200
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Hemorrhage and Use of Serotonin Reuptake Inhibitor Antidepressants in Pregnancy

Abstract: Serotonin-norepinephrine reuptake inhibitor exposure in late pregnancy was associated with a 1.6- to 1.9-fold increased risk of postpartum hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 43 publications
1
24
0
1
Order By: Relevance
“…Previous studies have reported differing risks of preeclampsia and PPH according to antidepressant class, for example, serotonin-norepinephrine reuptake inhibitors (SNRI) and tricyclic antidepressants were associated with stronger risks for preeclampsia than selective serotonin reuptake inhibitors (SSRI), 9,10 and SNRIs were associated with a stronger risk for PPH than SSRIs. 18 In a sensitivity analysis, we restricted to pregnancies exposed to SSRIs only; the study size was insufficient to compare non-SSRIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported differing risks of preeclampsia and PPH according to antidepressant class, for example, serotonin-norepinephrine reuptake inhibitors (SNRI) and tricyclic antidepressants were associated with stronger risks for preeclampsia than selective serotonin reuptake inhibitors (SSRI), 9,10 and SNRIs were associated with a stronger risk for PPH than SSRIs. 18 In a sensitivity analysis, we restricted to pregnancies exposed to SSRIs only; the study size was insufficient to compare non-SSRIs.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Some studies have found antidepressant exposure during pregnancy to be associated with a range of adverse perinatal outcomes including preeclampsia, especially for exposures into the second trimester, and postpartum haemorrhage (PPH), for late-pregnancy exposures. [8][9][10][11][12][13][14][15][16][17][18][19] Other studies,generally those with smaller numbers of exposed cases, conclude no association between antidepressants and preeclampsia and PPH. [20][21][22][23] Recently, studies have used longitudinal cluster analysis to classify medication use during pregnancy instead of a dichotomous "any use" versus "no use" approach.…”
Section: Introductionmentioning
confidence: 98%
“…When taken in late pregnancy, SSRIs may increase the risk of pulmonary hypertension in newborns and of postpartum bleeding in mothers (21). Sertraline, fluoxetine or citalopram at initial doses of 20 mg, with gradual dosage titration, are often recommended as a first-line therapy, since they pass into breast milk in minimal concentrations (22). Citalopram (at a maximum dose of 40 mg), escitalopram (at a maximum dose of 20 mg) and sertraline (at a maximum dose of 100 mg) are shown to be the safest during pregnancy, while fluvoxamine (at a daily dose of up to 300 mg), paroxetine (at a daily dose of up to 30 mg) and sertraline (at a daily dose of up to 100 mg) are recommended during the postpartum period in women who breast feed (23).…”
Section: Antidepressantsmentioning
confidence: 99%
“…One study reported no increased risk . However, controlled studies of SSRI use during late pregnancy have reported a significant increased risk for PPH (relative risk [RR], 1.53; 95% CI, 1.25‐1.86) and severe PPH (RR, 1.84; 95% CI, 1.39‐2.44) …”
Section: Ssris As First‐line Therapy During Pregnancy and Lactationmentioning
confidence: 99%